Microorganisms as biocontrol agents against bacterial citrus diseases - Poveda, Jorge (2021)
Citrus represents one of the most widely grown crops on the planet, extensively cultivated for both the fresh fruit and juice markets. The productivity of citrus orchards can be seriously affected by highly aggressive pathogenic bacteria, such as Xanthomonas citri subsp. citri, Xylella fastidiosa subsp. pauca and currently Candidatus Liberibacter asiaticus. Different microbiological biocontrol agents have been described against these pathogens, such as antagonistic bacteria (mainly species from Pseudomonas and Bacillus genus) and bacteriophages. This review summarizes all the microbiological control strategies reported so far against bacterial diseases that affect citrus, highlighting those fields of study where there is great potential yet to be discovered.